2021
DOI: 10.1515/eng-2021-0047
|View full text |Cite
|
Sign up to set email alerts
|

Testing and evaluation of cold-start emissions from a gasoline engine in RDE test at two different ambient temperatures

Abstract: In order to better reflect the actual ecological performance of vehicles in traffic conditions, both the emission standards and the applied emission tests are being developed, for example by considering exhaust emissions for a cold engine start. This article presents the research results on the impact of ambient temperature during the cold start of a gasoline engine in road emission tests. The Real Driving Emissions (RDE) tests apply to passenger cars that meet the Euro 6 emissions norm and they are complement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Higher percentages were measured at lower ambient temperatures. For the actual on-road tests, the contribution was 6-19% for CO and NO x , which is in agreement with other studies [56,60].…”
Section: Cold Startsupporting
confidence: 92%
See 2 more Smart Citations
“…Higher percentages were measured at lower ambient temperatures. For the actual on-road tests, the contribution was 6-19% for CO and NO x , which is in agreement with other studies [56,60].…”
Section: Cold Startsupporting
confidence: 92%
“…For NO x , the contribution was lower in most RDE short tests. Other studies have also found a high contribution from cold start for CO (>70%), but this is smaller for NO x (40-60%) for turbo-charged GDI vehicles [53][54][55]; however, lower percentages have also been reported for RDE trips [32,56]. The cold start contribution was around 50% for NH 3 .…”
Section: Cold Startmentioning
confidence: 89%
See 1 more Smart Citation
“…Since cold start and ambient temperature are closely related and have a large influence on each other, we also included cold start emissions in the study. The contribution of cold start for petrol vehicles was also investigated in the work by Pielecha et al ( 2021 ). The authors found that at 8 °C (the lowest temperature studied), the proportion of cold start emissions was highest as a function of total driving emissions.…”
Section: Methodsmentioning
confidence: 99%
“…Normally, catalytic converter has low efficiency of CO conversion in low temperature and the efficiency will be increased along with the increasing of temperature [19]. According to research, a gasoline car emits may emits CO with the concentration of 1 % in the first minute of idling and it gradually reduces the CO concentration as the increase of engine and catalytic converter temperature [20].…”
Section: Introductionmentioning
confidence: 99%